Resper: aplicação móvel para reserva de salas e auditórios para reuniões e eventos - COSTA, Marcos Fernando Soares (2023)
With the advancement of mobile applications, solutions to different types of problems in different professional areas emerge. These solutions can range from a simple calendar to register events to an application that makes purchases of meals in different restaurants. Within this context, this work aims to present the construction of a mobile application, called Resper System, which aims to help employees (teachers and administrative assistants) of the Federal University of Pará - Campus Castanhal, in booking rooms and auditoriums for of meetings and events, seeking to help users to deal with room allocation problems and, to keep abreast of the happening of events and meetings that take place within the campus. The prototype has Android systems, and is working on devices that have the Android Nougat version (Android 7.0) or higher. The information recorded within the application is stored in the Firebase database. The application results demonstrated a satisfactory operation compared to the defined modeling requirements and diagrams.